(untitled) (American Journal of Technology and Applied Sciences, 2025)
The current legislation of Uzbekistan has introduced a number of dispute resolution procedures. This is due to the fact that in recent years, in the practice of law enforcement, the parties have been preferring to use the most alternative methods of resolving legal disputes. In our opinion, one of the most acceptable methods of pre-trial resolution of legal disputes is the institution of mediation, which does not bypass family relations.